Interleukin-24 Regulates T Cell Activity in Patients With Colorectal Adenocarcinoma - Zhang, Yang; Liu, Ye; Xu, Yuechao (Frontiers in Oncology, 2019)
Interleukin (IL)-24 plays a potential anti-tumor activity in colorectal cancer in a dose-dependent manner. However, the immunoregulatory role of IL-24 to peripheral and tumor-infiltrating T cell function in colorectal cancer was not fully elucidated. In this study, twenty-nine colorectal adenocarcinoma patients and fifteen healthy individuals were enrolled. IL-24 expression and IL-24 receptor (IL-20R1, IL-20R2, and IL-22R1) mRNA relative level was measured by ELISA and real-time PCR, respectively. CD4+ and CD8+ T cells were purified from peripheral bloods and cancer specimens, and were stimulated with low (10ng/ml) and high (100ng/ml) concentration of recombinant IL-24. CD4+ T cells activity was assessed by measurement of Th cell percentage, transcriptional factors, and cytokine production. CD8+ T cells activity was evaluated by investigation of cytotoxic molecules, target cell death, and interferon-γ (IFN-γ) secretion. IL-24 was decreasingly expressed in both peripheral bloods and cancer tissues in colorectal adenocarcinoma patients. However, IL-20R1 and IL-20R2 was comparable between healthy controls and colorectal adenocarcinoma patients. Low concentration of IL-24 suppressed CD4+ T cell proliferation. In contrast, high concentration of IL-24 not only promoted CD4+ T cell proliferation, but also enhanced CD4+ T cell activity, which mainly presented as up-regulation of Th1/Th17 frequency, T-bet/RORγt mRNA, and IFN-γ/IL-17 production but down-regulation of Treg percentage, FoxP3 mRNA, and IL-10/IL-35 secretion. Moreover, high concentration of IL-24 also increased perforin and granzyme B expression in CD8+ T cells, and elevated cytolytic and non-cytolytic activity of CD8+ T cells, which presented as induction of target cell death and elevation of IFN-γ expression. However, low concentration of IL-24 did not affect bioactivity of CD8+ T cells. The current data indicated that IL-24 might regulate T cell function in a dose-dependent manner. High-concentration of IL-24 might promote anti-tumor immune responses in development novel therapeutic approaches to colorectal adenocarcinoma.